Evaluation the potential and energy efficiency of dual stage pressure retarded osmosis process. (1st August 2017) - Altaee, Ali; Zaragoza, Guillermo; Drioli, Enrico; Zhou, John
Graphical abstract: Highlights: Single and dual stage PRO was evaluated at different membrane configurations. Impact of increasing module area or numbers on the power efficiency was studied. DSPRO reduced the impact of CP & restored the osmotic potential of salinity gradient. DSPRO outperforms single stage PRO process but depends on salinity gradient type. Abstract: Power generation by means of Pressure Retarded Osmosis (PRO) has been proposed for harvesting the energy of a salinity gradient. Energy recovery by the PRO process decreases along the membrane module due to depleting of the chemical potential across the membrane and concentration polarization effects. A dual stage PRO (DSPRO) design can be used to rejuvenate the chemical potential difference and reduce the concentration polarization on feed solution. Several design configurations were suggested for the membrane module arrangements in the first and second stage of the PRO process. PRO performance was evaluated for a number of salinity gradients proposed by coupling Dead Sea water or Reverse Osmosis (RO) brine with seawater or wastewater effluent. Maximum specific energy of inlet and outlet feeds was calculated using a developed computer model to identify the amount of recovered and remaining energy. Initially, specific power generation by the PRO process increased by increasing the number of modules of the first stage. Maximum specific energy is calculated along the PRO module to understand the degradation of the maximum specific energy in each module before introducing a second stage PRO process. Adding a second stage PRO process resulted in a sharp increase of the chemical potential difference and the specific energy yield of the process. Between 10% and 13% increase of the specific power generation was achieved by the DSPRO process for the Dead Sea-seawater salinity gradient depending on the dual stage design configuration. For Dead Sea-RO brine, 12–16% increase of the specific power generation was achieved by the dual stage PRO process. For Dead Sea-wastewater and RO brine-wastewater, a neutral and sometimes negative impact occurred when a second stage PRO process was introduced. We concluded that, for a given draw solution concentration, dual stage performs better than the conventional PRO process at high feed salinities, yet requires lower hydraulic pressure.